Displacement and Mixing of Blasted Sedimentary Rocks in Quarrying - Stephen Chung; Scott Gosch; John Carpenter; James Breedlove (International Society of Explosives Engineers, 2001)
While controlling fly rock and ground vibration in quarrying in the neighborhood of a residential area, producing good fragmentation and keeping different grades of material separated in a muckpile are important in maintaining the productivity of quality aggregates. This paper describes a single row production blast for the study of fragmentation and displacement in the grade control carried out at a quarry of Barrett Paving Materials Inc. in Sylvania, Ohio. Digital video imaging was used to monitor the blast-induced motion of the bench face as input to the DMC_Blast (Distinct Motion Code), for the analysis of the formation of the muckpile. The actual digitized blast video and the DMC_Blast simulation are compared. The displacement and mixing of all the inter-bedded limestone layers are made visible in the simulated cross-section of the muckpile. The apparent fragmentation analysed with PowerSieve is also discussed.